1989
DOI: 10.1007/bf02535212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium deficiency on Δ6 desaturase activity and fatty acid composition of rat liver microsomes

Abstract: Experimental Mg2+ deficiency was induced in a group of rats by feeding them a Mg2+-deficient diet for 23 days. They were pair-fed to compare with a control group of rats fed a Mg2+-sufficient diet. In the Mg2+-deficient group the plasma total cholesterol and triglyceride levels were increased while HDL-cholesterol was decreased. In the Mg2+-deficient group the plasma level of thiobarbituric acid reacting substances (TBARS) used as a measure for lipid peroxidation was increased. The increase was attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…These early findings were then corroborated by other authors (15)(16)(17). Similarly, the effect of magnesium as an essential cofactor in the fatty acid oxidative desaturation reactions was previously reported (1,18). Τhe ∆5 and ∆9 desaturation steps are also particularly influenced by the level of copper, which has an opposite effect to that of zinc (19)(20)(21)(22)(23)(24)(25)(26).…”
supporting
confidence: 81%
“…These early findings were then corroborated by other authors (15)(16)(17). Similarly, the effect of magnesium as an essential cofactor in the fatty acid oxidative desaturation reactions was previously reported (1,18). Τhe ∆5 and ∆9 desaturation steps are also particularly influenced by the level of copper, which has an opposite effect to that of zinc (19)(20)(21)(22)(23)(24)(25)(26).…”
supporting
confidence: 81%
“…We, as well as others (5,29, 41), have reported that Mg deficiency may promote hyperlipidemia. Moreover, an earlier study indicated that Mg supplementation could attenuate diet-induced triglyceridemia in a rabbit model (3).…”
supporting
confidence: 52%
“…Mg may play a key role in the regulation of carbohydrate and lipid metabolism (44,45). Severe magnesium deficiency can promote lipogenesis (5,29,41). In the present study, RTV treatment alone decreased circulating Mg levels, but this decrease was mild (Ϫ12%) and may not be the major cause leading to hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cross-sectional data obtained from 123 subjects in Korea indicated that there was no significant difference in Mg concentrations between the MetS group and the control group [45] . Deficiency in blood concentrations of Mg has been reported to affect the activities of enzymes and cause metabolic disorders [46][47][48] . However, in this study, we observed opposite correlations between Mg and BMI, blood pressure, blood lipid and blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%